Prevalence and risk factors of unsuppressed viral load among pregnant and breastfeeding women in sub-Saharan Africa: analysis from population-based surveys. (15th March 2023) - Schrubbe, Leah A.; Stöckl, Heidi; Hatcher, Abigail M.; Marston, Milly; Kuchukhidze, Salome; Calvert, Clara
Abstract : Objective: To examine the prevalence of viral suppression and risk factors for unsuppressed viral load among pregnant and breastfeeding women living with HIV (WLH). Design: Pooled analysis among pregnant and breastfeeding WLH from Population-Based HIV Impact Assessment (PHIA) cross-sectional surveys from 10 sub-Saharan African countries. Methods: Questionnaires included sociodemographic, relationship-related, and HIV-related items, while blood tests examined HIV serostatus and viral load (data collected 2015–2018). The weighted prevalence of viral suppression was calculated. Logistic regression was used to examine risk factors for unsuppressed viral load (≥1000 copies/ml). Results: Of 1685 pregnant or breastfeeding WLH with viral load results, 63.8% (95% confidence interval (CI): 60.8–66.7%) were virally suppressed at the study visit. Among all included women, adolescence (adjusted odds ratio (aOR): 4.85, 95% CI: 2.58–9.14, P  < 0.001) and nondisclosure of HIV status to partner (aOR: 1.48, 95% CI: 1.02–2.14, P  = 0.04) were associated with unsuppressed viral load. Among only partnered women, adolescence (aOR: 7.95, 95% CI: 3.32–19.06, P  < 0.001), and lack of paid employment (aOR: 0.67, 95% CI: 0.47–0.94, P  = 0.02) were associated with unsuppressed viral load. Examining only women on ART, nondisclosure of HIV status to partner (aOR: 1.85, 95% CI: 1.19–2.88, P  = 0.006) was associated with unsuppressed viral load. Conclusion: Viral suppression among pregnant and breastfeeding WLH in sub-Saharan Africa remains suboptimal. Relationship dynamics around nondisclosure of HIV-positive status to partners was an important risk factor for unsuppressed viral load. Improving HIV care via sensitive discussions around partner dynamics in pregnant and breastfeeding women could improve maternal HIV outcomes and prevention of mother-to-child transmission of HIV (PMTCT).